Outcome and Genetic Factors in IgG4-Associated Autoimmune Pancreatitis and Cholangitis: A Single Center Experience - Matthias Buechter; Paul Manka; Falko Markus Heinemann; Monika Lindemann; Benjamin Juntermanns; Ali Canbay; Guido Gerken; Alisan Kahraman (Gastroenterology Research and Practice)
Introduction. Most investigations on autoimmune pancreatitis (AIP) were published on Asian cohorts while those on Caucasians are limited. However, there might be differences related to the origin. Patients and Methods. We analyzed 36 patients and compared type 1 (AIP1) with type 2 (AIP2). Results. The majority of patients suffered from AIP1 (55.6%). AIP1 patients were significantly older than AIP2 patients (54.4 versus 40.8 years). Moreover, 85.0% of AIP1 patients had concurrent autoimmune cholangitis (AIC) while 18.8% of AIP2 patients suffered from overlap to ulcerative colitis (UC). However, AIP1 patients revealed a cholestatic course and had significantly higher immunoglobulin G4 levels (IgG4). When compared to allele frequencies in healthy controls, in patients with AIP1 HLA-B8 reached statistical significance. Response to steroids was excellent in both groups, but we noticed high rates of relapse especially in AIP1 patients. Finally, 3 patients with AIP1 were diagnosed with cholangiocellular carcinoma (CCC). Conclusion. In contrast to Asian studies, we found an almost equal distribution of AIP1 and AIP2 patients in our German cohort. AIP2 patients were younger and mostly of female gender whereas AIP1 patients revealed higher IgG4 levels and involvement of the biliary tract in sense of IgG4-associated cholangitis.